Selection of indicators for assessing and managing the impacts of bottom trawling on seabed habitats. Issue 7 (17th April 2020) - Hiddink, Jan Geert; Kaiser, Michel J.; Sciberras, Marija; McConnaughey, Robert A.; Mazor, Tessa; Hilborn, Ray; Collie, Jeremy S.; Pitcher, C. Roland; Parma, Ana M.; Suuronen, Petri; Rijnsdorp, Adriaan D.; Jennings, Simon
Abstract: Bottom trawl fisheries are the most widespread source of anthropogenic physical disturbance to seabed habitats. Development of fisheries‐, conservation‐ and ecosystem‐based management strategies requires the selection of indicators of the impact of bottom trawling on the state of benthic biota. Many indicators have been proposed, but no rigorous test of a range of candidate indicators against nine commonly agreed criteria (concreteness, theoretical basis, public awareness, cost, measurement, historical data, sensitivity, responsiveness, specificity) has been performed. Here, we collated data from 41 studies that compared the benthic biota in trawled areas with those in control locations (that were either not trawled or trawled infrequently), examining seven potential indicators (numbers and biomass for individual taxa and whole communities, evenness, Shannon–Wiener diversity and species richness) to assess their performance against the set of nine criteria. The effects of trawling were stronger on whole‐community numbers and biomass than for individual taxa. Species richness was also negatively affected by trawling but other measures of diversity were not. Community numbers and biomass met all criteria, taxa numbers and biomass and species richness satisfied most criteria, but evenness and Shannon–Wiener diversity did not respond to trawling and only met few criteria, and hence are not suitable state indicators of the effect of bottom trawling. Synthesis and applications . An evaluation of each candidate indicator against a commonly agreed suite of desirable properties coupled with the outputs of our meta‐analysis showed that whole‐community numbers of individuals and biomass are the most suitable indicators of bottom trawling impacts as they performed well on all criteria. Strengths of these indicators are that they respond strongly to trawling, relate directly to ecosystem functioning and are straightforward to measure. Evenness and Shannon–Wiener diversity are not responsive to trawling and unsuitable for the monitoring and assessment of bottom trawl impacts. Abstract : An evaluation of each candidate indicator against a commonly agreed suite of desirable properties coupled with the outputs of our meta‐analysis showed that whole‐community numbers of individuals and biomass are the most suitable indicators of bottom trawling impacts as they performed well on all criteria. Strengths of these indicators are that they respond strongly to trawling, relate directly to ecosystem functioning and are straightforward to measure. Evenness and Shannon–Wiener diversity are not responsive to trawling and unsuitable for the monitoring and assessment of bottom trawl impacts. Samenvatting: Bodemtrawlvisserij is de grootste bron van antropogene fysieke verstoring van de zeebodemhabitats. Ontwikkeling van strategieën voor visserij en ecosystemen vereist de selectie van indicatoren voor de impact van bodemtrawling op de toestand van benthische biota. Er zijn veel verschillende indicatoren voorgesteld, maar tot nu toe er is geen rigoureuze toetsing van een reeks kandidaat‐indicatoren aan de hand van 9 algemeen overeengekomen criteria uitgevoerd (concreetheid, theoretische basis, publiek bewustzijn, kosten, meting, historische gegevens, gevoeligheid, responsiviteit, specificiteit). Hier hebben we gegevens verzameld van 41 studies die de benthische biota in gebieden met bodembevissing vergeleken met die op controlelocaties (die niet of weinig bevist waren), waarbij we 7 mogelijke indicatoren (aantallen en biomassa voor individuele taxa en hele gemeenschappen, Evenness, Shannon‐Wiener‐diversiteit en soortenrijkdom) om hun prestaties te beoordelen aan de hand van 9 criteria. De effecten van trawling waren sterker op de totale gemeenschap en op biomassa dan voor individuele taxa. De soortenrijkdom werd ook negatief beïnvloed door trawlvisserij, maar andere maatstaven voor diversiteit niet. Aantallen en biomassa voor de gemeenschap voldeden aan alle criteria, taxa‐aantallen en biomassa en soortenrijkdom voldeden aan de meeste criteria, maar Evenness en Shannon‐Wiener‐diversiteit reageerden niet op trawling en voldeden slechts aan enkele criteria, en zijn daarom geen geschikte statusindicatoren van het effect van bodemtrawls. Synthese en toepassingen. Een evaluatie van elke kandidaat‐indicator aan de hand van een algemeen overeengekomen reeks gewenste eigenschappen in combinatie met de resultaten van onze meta‐analyse toonde aan dat het totale aantal individuen en biomassa in de hele gemeenschap de meest geschikte indicatoren zijn voor bodemtrawlingeffecten, aangezien ze goed presteerden op alle criteria. Sterke punten van deze indicatoren zijn dat ze sterk reageren op trawling, direct verband houden met het functioneren van het ecosysteem en eenvoudig te meten zijn. Evenness en Shannon‐Wiener diversiteit reageren niet op bodembevissing en zijn niet geschikt voor het monitoren en beoordelen van bodemtrawleffecten.